2020
DOI: 10.3390/app10124291
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Urine Flow with Multiple Sizes of Double-J Stents

Abstract: This study investigated which sizes of double-J stents are more effective in achieving an acceptable urine flow through stenotic and stented ureters. Sixty four computational fluid dynamics models of the combinations of two different gauge ureters (4.57 mm and 5.39 mm in diameter) with four different levels of ureteral and four different sizes of double-J stents were developed for the numerical analysis of urine flow in the ureter. Luminal, extraluminal, and total flow rates along the ureter were measured, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Notably, the majority of side-holes experienced WSS levels that are anticipated to favor significant accumulation of crystals and may, therefore, suffer from partial or complete occlusion. 19 Previous computational studies have also consistently shown that a significant proportion of side-holes is not involved in flow exchange between the stent and ureter; 12,18,38 however, the correlation between WSS levels and particle accumulation at side-holes within a full-scale model of the stented ureter has not been previously investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the majority of side-holes experienced WSS levels that are anticipated to favor significant accumulation of crystals and may, therefore, suffer from partial or complete occlusion. 19 Previous computational studies have also consistently shown that a significant proportion of side-holes is not involved in flow exchange between the stent and ureter; 12,18,38 however, the correlation between WSS levels and particle accumulation at side-holes within a full-scale model of the stented ureter has not been previously investigated.…”
Section: Resultsmentioning
confidence: 99%
“… 11 In a more recent CFD investigation, the same group evaluated the flow performance of stents with differing diameter, using ureter models presenting varying levels of stenosis. 12 Stents with smaller diameter had superior drainage performance, including within ureter models presenting mild-to-severe stenoses. Further investigations on the function of side-holes and urine flow distribution in the stented ureter have been carried out in a CFD study by Amitay-Rosen et al 13 Their numerical model replicated either a circumferential occlusion of the ureter or an external pressure applied on one side of the ureter wall.…”
Section: Introductionmentioning
confidence: 97%
“…According to previous studies, the ureter tapers caudally from the pyeloureteral transition (5.67 ± 0.94 mm) to a small diameter (3.96 ± 0.65 mm) at the lower pole of the kidney. It then widens to its maximum diameter (5.11 ± 1.34 mm) at the abdominal ureter and retracts (3.59 ± 1.20 mm) at the pelvic margin across the common iliac artery( 19 , 20 ) ( Figure 2A ). The ureter was dissected at the lower level of the common iliac artery (median length of the removed ureter: 115.0 cm [95% CI, 100.0∼125.0 cm]) by the same surgeon, similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Most urological procedures and treatments, such as lithotripsy, ureteroscopic procedures, prevention of ureteral stenosis, relief of hydronephrosis, and reduction in urological complications, require double-J (DJ) stents[ 1 - 7 ]. In general, these DJ stents are thin and hollow tubes with side holes composed of polyurethane material, and both ends are rolled up to hold the stent in the ureter[ 8 ]. The DJ stents are located in the ureter to enable urine drainage from the kidney into the bladder and to prevent contraction of the ureter after the removal of urinary stones[ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%